Lecturers’ Perspectives on the effectiveness of Modular-Based Teaching in Higher Education in Zimbabwe - Mqemane Tshababa; Mokoena P Maepa; Owen Mukwawaya; Tapiwa Betera (Studies in Learning and Teaching, 2026)
Most higher learning institutions in Zimbabwe have adopted a modular based teaching approach in line with the Ministry of Higher and Tertiary Education, Innovation, Science and Technology Development’s Education 5.0 Philosophy. The present study aimed to gather the qualitative insights from lecturers regarding the effectiveness of modular based teaching approach at one public university in Zimbabwe. The study used a qualitative approach and a case study design to solicit for lecturers’ perspectives on the effectiveness of modular based teaching approach at university level. Twelve participants were purposively selected from across six university faculties to respond to interview questions. Each faculty provided two participants. The participants had qualifications ranging from Master’s degree to Professorship. The data for the study was collected using an interview guide. The interview was conducted face to face with the participating lecturers. The generated data were analysed thematically using N-vivo version 15. The study found there are both opportunities and challenges to the teaching and learning experiences brought about by modular based teaching. The study also found that the modular based teaching was only as effective as students were able to effectively manage time. In addition, the study found that for modular based teaching to be effective there is a need for the deployment of resources to support modular based teaching through online learning platforms like Moodle. Based on the key findings of the study, it is recommended that the modular based teaching adopt artificial intelligence (AI) as part of teaching instruction evolution and innovation.